2021
DOI: 10.1093/infdis/jiab302
|View full text |Cite
|
Sign up to set email alerts
|

Proper Assignation of Reactivation in a COVID-19 Recurrence Initially Interpreted as a Reinfection

Abstract: A 77-year-old-male (Case R) who had had a previous diagnosis of mild COVID-19 episode, was hospitalized 35 days later. On Day 23 post-admission, he developed a second COVID-19 episode, now severe, and finally died. Initially, Case R COVID-19 recurrence was interpreted as a reinfection due to the exposure to a SARS-CoV-2 RT-PCR-positive room-mate. However, whole-genome-sequencing indicated that case R recurrence corresponded to a reactivation of the strain involved in his first episode. Case R reactivation had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Long viral shedding has already been reported, as well as intra-host viral evolution, but mainly in immunocompromised patients ( Choudhary et al, 2021 ). Otherwise, new symptomatology arising in a previous positive case could be due to a COVID-19 reactivation, as has been described clinically and confirmed by sequencing ( Chen et al, 2021 ; Lee J. T. T. et al, 2021 ; Pérez-Lago et al, 2021 ) occurring at a median of 57 days. In the present study, among confirmed reinfection cases with compatible symptoms in the second episode, two of them occurred as soon as 55 and 63 days (cases P9 and P16) after the first episode, but they were confirmed due to the higher number of mutations than the expected by the natural evolution of the virus.…”
Section: Discussionmentioning
confidence: 66%
“…Long viral shedding has already been reported, as well as intra-host viral evolution, but mainly in immunocompromised patients ( Choudhary et al, 2021 ). Otherwise, new symptomatology arising in a previous positive case could be due to a COVID-19 reactivation, as has been described clinically and confirmed by sequencing ( Chen et al, 2021 ; Lee J. T. T. et al, 2021 ; Pérez-Lago et al, 2021 ) occurring at a median of 57 days. In the present study, among confirmed reinfection cases with compatible symptoms in the second episode, two of them occurred as soon as 55 and 63 days (cases P9 and P16) after the first episode, but they were confirmed due to the higher number of mutations than the expected by the natural evolution of the virus.…”
Section: Discussionmentioning
confidence: 66%
“…The infectious lineages were not sequenced. As a result, it cannot be completely ruled out that a case's recurrence corresponds to a reactivation of the strain involved in its first episode (48,49); 2. The number of cases was relatively small; 3.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, reactivation or relapse takes place mainly after recovering from an infection, the patient retests positive with the same viral clade or develops clinical symptoms no longer than 60 days and mainly occurred 10–27 days after infection added by lack of exposure with infected ones or exposure to infected ones with the virus from different clade [ 15 , 17 , 18 ]. In general, reactivation is more common in immunosuppressed patients [ 19 ]. This may be because of an unresolved viral infection that was not detected after two negative RT-PCR tests.…”
Section: Criteria For True Reinfection and Reactivation Of The Virusmentioning
confidence: 99%